Solvability of a Class of Generalized Neumann Boundary Value Problems for Second-Order Nonlinear Difference Equations - Jianye Xia; Yuji Liu (Discrete Dynamics in Nature and Society)
This paper is motivated by Rachnkovab and Tisdell (2006) and Anderson et al. (2007). New sufficient conditions for the existence of at least one solution of the generalized Neumann boundary value problems for second order nonlinear difference equations ∇Δx(k)=f(k,x(k),x(k+1)), k∈[1,n−1], x(0)=ax(1), x(n)=bx(n−1), are established.